Linezolid and tedizolid adverse effects: a review on serotonin syndrome, myelosuppression, neuropathies, and lactic acidosis - Adam Greenfield; Erin Deja; Kimberly Lee; Sangeeta Sastry; Barry Rittmann (Antimicrobial Stewardship & Healthcare Epidemiology)
Oxazolidinone antibiotics—linezolid and tedizolid—are often used to treat multidrug-resistant infections. They are highly bioavailable and ideal for transition to enteral therapy when appropriate. However, multiple associated adverse effects are potentially treatment-limiting. The objective of this review is to discuss relevant adverse effects of linezolid and tedizolid, including serotonin syndrome, myelosuppression, neuropathies, and lactic acidosis, and their commonality in real-world experience in the last decade. Mitigation strategies, including the role of therapeutic drug monitoring, are also discussed.